The Role of Multiliteracy Based on Interactive Learning Media in PAI Learning in Elementary Schools - Wahyu Eko Purwanto; Siti Roudhotul Jannah; Eka Fitria Ningsih (Assyfa Journal of Islamic Studies, 2026)
This research is motivated by the low interest of students in learning Islamic Religious Education (PAI) at SD Negeri 6 Tanjung Raya, which is reflected in the lack of active participation, attention, and involvement of students in the learning process. Amidst the development of technology and the flow of digital information, students are required to have multiliteracy skills that include reading and writing literacy, digital literacy, visual literacy, and media literacy. This study aims to analyze the role of interactive learning media-based multiliteracy in increasing student learning interest, as well as identifying its implementation and impact on learning engagement in PAI learning in elementary schools. This study uses a descriptive qualitative approach with a case study type. The research subjects include the principal, PAI teachers, and students in grades IV and V. Data collection techniques were carried out through in-depth interviews, participatory observation, and documentation studies. Data validity was tested using triangulation of sources, techniques, and time, as well as member checks. Data analysis used the Miles and Huberman interactive model which includes data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of interactive media-based multiliteracy at SD Negeri 6 Tanjung Raya has been running, although not evenly distributed. The media used include educational videos, visual presentations, digital quizzes, and learning simulations. Multiliteracies play a significant role in improving the quality of Islamic Religious Education (PAI) learning by presenting abstract material in a more concrete and engaging manner. The use of interactive media has been shown to positively impact student learning interest, as evidenced by increased participation, enthusiasm, and courage in expressing opinions.